Antimicrobial activity of cotton fabric treated with extracts from the lotus plant. Issue 15 (September 2014) - Oh, Kyung Wha; Na, Young Joo
This study evaluated the application of medicinal plants to fabric finishes and the functionality of the fabrics finished with ethanolic extracts of the lotus plant, such as lotus leaf, lotus pot and lotus seed. Treated cotton was dyed a light orange and yellow-green color using lotus pot and lotus leaf, respectively, and the color difference (Δ E ) of fabrics before/after treatment with extract solution of lotus leaf was a maximum of 36.4. When the processing concentration of extract solution and treatment temperature of cotton fabric were increased, the color and color ingredient uptake increased, but the optimal processing time was found to be 30 minutes. Regarding the dyeing properties, the fabrics treated with the lotus leaf extract showed the best color in terms of color intensity, whereas the antibacterial activity was highest in the case of fabric treated with lotus pot extract. Antibacterial activity was significant in the order of lotus pot > lotus leaf > lotus seed. The fabric treated with the lotus leaf extract exhibited significant antibacterial activity only when it was treated at high concentrations (>8%), whereas the fabric treated with the lotus pot extract showed significant antibacterial activity even when treated at low concentrations (4%) or low temperatures (40℃). Accordingly, ethanolic lotus pot extract is recommended as an environment-friendly antibacterial finishing.